Simultaneous Liver Venous Deprivation Following Hepatic Arterial Chemoembolization Before Major Hepatectomy for Hepatocellular Carcinoma: A New Methods to Achieve Hypertrophy Liver Remnant - Zhang S; Song R; Hou C; Yao H; Xu J; Zhou H; Li S; Cai W; Fei Y; Meng F; Yin D; Wang J; et al. (Journal of Hepatocellular Carcinoma)
Shenyu Zhang,1,* Ruipeng Song,1,* Changlong Hou,2,* Huanzhang Yao,1 Jun Xu,2 Hangcheng Zhou,3 Shaopeng Li,4 Wei Cai,1 Yipeng Fei,2 Fanzheng Meng,1 Dalong Yin,1 Jiabei Wang,1 Shugeng Zhang,1 Yao Liu,1 Jizhou Wang,1,5,6 Lianxin Liu1,5,6 1Department of Hepatobiliary Surgery, Centre for Leading Medicine and Advanced Technologies of IHM, the first affiliated hospital of ustc, Division of Life Sciences and Medicine, university of science and technology of china, Hefei, Anhui, 230001, People’s Republic of China; 2Department of Intervention, The First Affiliated Hospital of USTC: Anhui Provincial Hospital, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, Anhui, 230001, People’s Republic of China; 3Department of Pathology, The First Affiliated Hospital of USTC: Anhui Provincial Hospital, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, Anhui, 230001, People’s Republic of China; 4Department of Imaging, The First Affiliated Hospital of USTC: Anhui Provincial Hospital, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, Anhui, 230001, People’s Republic of China; 5Anhui Provincial Key Laboratory of Hepatopancreatobiliary Surgery, Hefei, Anhui, 230001, People’s Republic of China; 6Anhui Provincial Clinical Research Center for Hepatobiliary Diseases, Hefei, Anhui, 230001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lianxin Liu; Jizhou Wang, Email liulx@ustc.edu.cn; wangjoe@ustc.edu.cnPurpose: Liver venous deprivation (LVD; simultaneous portal vein embolization and hepatic vein embolization) has been the latest surgical strategy for rapid future liver remnant (FLR) hypertrophy. The aim of this study was to assess the feasibility, safety, and efficacy of simultaneous LVD following hepatic arterial chemoembolization (TACE-LVD) before major hepatectomy for hepatocellular carcinoma (HCC).Patients and Methods: A retrospective analysis of the outcomes of 23 HCC patients who underwent TACE-LVD at our center between October 2019 and October 2023 was conducted. An assessment of postoperative complications, FLR volume, liver function, and tumor response was performed.Results: All patients successfully underwent TACE-LVD. No other serious complications occurred except in 1 patient who underwent puncture drainage due to excessive pleural effusion. Following TACE-LVD, transaminase levels peak two days before rapidly decreasing and return to preoperative levels within one week. The ratio of FLR to standardized liver volume increased from 35.9% (interquartile range [IQR], 8.6) to 46.4% (IQR, 8.2), with a mean degree of hypertrophy and kinetic growth rate of 13.2% (IQR, 5.4) and 4.4% (IQR, 1.8) per week, respectively. At the first assessment after TACE-LVD, most patients exhibited sufficient FLR for hepatectomy, except for 4 patients with cirrhosis. The modified response evaluation criteria for solid tumor assessment revealed a disease control rate of 95.7%, with only 1 patient (Barcelona Clinic Liver Cancer stage C) developing intrahepatic disease progression.Conclusion: TACE-LVD seems to be a feasible, safe, and effective strategy for rapid FLR hypertrophy. Moreover, TACE-LVD may be a therapeutic choice if insufficient FLR hypertrophy precludes resection. This strategy warrants further exploration.Keywords: hepatocellular carcinoma, hepatectomy, liver hypertrophy, liver venous deprivation, arterial chemoembolization